Ecophysiology of dryland corn and grain sorghum as affected by alternative planting geometries and seeding rates - Haag, Lucas A. (Kansas State University, 2013)
Previous work in the High Plains with alternative planting geometries of corn and grain sorghum has shown potential benefits in dryland production. Studies conducted in 2009-2011 at Tribune, KS evaluated five planting geometries in corn and grain sorghum: conventional, clump, cluster, plant-one skip-one (P1S1), and plant-two skip-two (P2S2). Geometries were evaluated at three plant densities in corn: 3.0, 4.0, and 5.1 plants m[superscript]-2. Every measured corn production characteristic was affected by planting geometry, seeding rate, or an interaction in at least one of the years. Corn planted in a P2S2 configuration produced the least above-ground biomass, kernels plant[superscript]-1, kernels ear row[superscript]-1, and the highest kernel weight. Conventionally planted corn minimized harvest index and maximized stover production. Alternative geometries produced similar harvest indices. Grain yield response to seeding rate varied by geometry and year. Responsiveness and contribution of yield components were affected by geometry. Yield and yield components, other than ears plant[superscript]-1, were the least responsive to seeding rate in a cluster geometry. Clump planting consistently maximized kernels plant[superscript]-1. Prolificacy was observed in the cluster treatment and barrenness in the skip-row treatments. Light interception at silking was highest for clump and conventional geometries and lowest for the skip-row treatments. Corn in a P2S2 configuration did not fully extract available soil water. Conventionally planted corn had the lowest levels of soil water at tassel-silk indicating early-season use which potentially affected kernel set. In the lowest yielding year, grain water use efficiency was highest for clump and P2S2. Across-years, grain yields were lower for corn planted in a P2S2 geometry. Across-years corn yields were maximized when planted in clump at low or intermediate plant density, conventional and P1S1 at low plant density, P1S1 at high density, or cluster at any density. Planting grain sorghum in a P1S1 or P2S2 configuration reduced total biomass, grain yield, water use efficiency for grain production (WUEg), and water use efficiency for biomass production (WUEb) compared to conventional, clump, or cluster geometries at the yield levels observed in this study. Total water use was unaffected by planting geometry although cumulative water use at flower / grain fill was higher for conventional, clump, and cluster than for skip-row configurations. Sorghum planted in a conventional geometry was always in the highest grouping of grain yields. Grain yields from sorghum in either a cluster or clump geometry were each in the top yield grouping two of three years. When evaluated across-years, sorghum planted in a clump, cluster, or conventional geometry resulted in similar levels of above-ground biomass, grain yield, WUEg, and WUEb. Clump or cluster planting appear to have substantially less downside in a high yielding year than skip-row configurations. A comparison of corn and sorghum reinforced the findings of others that the relative profitability of the crops is largely dependent on the environment for any given crop year. Relative differences in grain yield, WUEg, WUEb, and net returns varied by year. Net returns over the three year study were maximized by conventional, cluster, and clump planted sorghum as well as clump planted corn.
Keywords: Dryland corn grain; Sorghum planting geometry; Agronomy (0285)